Modal analysis of silicon-on-insulator based rib waveguide using fully vectorial finite-difference mode solver. (1st December 2022) - Kumari, Shayna; Prince, Shanthi
Abstract: In order to interface optical integrated devices with external sources, an understanding of the modal characteristics of the optical waveguide is essential. The finite difference approach is utilized in this work to analyse a rib waveguide based on a silicon-on-insulator platform. A silicon device layer with thickness of 220 nm and a buried oxide with thickness of 2000 nm are considered. It is important to study the modal field distribution and parameters of the waveguide. The simulation results on the behaviour of modal parameters show that both effective refractive index and group index decrease with wavelength. The effective refractive index of the guided mode increases with rib width and slab thickness. It is also observed that energy is more confined in a deeply etched waveguide than in a shallow etched waveguide. Additionally, it is noted that the effective mode area and full-width half maximum increase with rib width and slab thickness.